Single-Stage Total Earlobe Reconstruction in a Young Male: A Case Report - Giri, Piyush; Pokhrel, Shrinkhala; Pandey, Pratishtha; Kunwar, Sushma; Khadka, Karuna (Nepal Medical College Journal, 2024)
This case report details a young male patient’s successful single-stage total earlobe reconstruction. The patient, a 24-year-old male, presented with a near complete earlobe loss following a traumatic injury. Utilizing an innovative surgical technique, the reconstruction achieved excellent cosmetic and functional outcomes, demonstrating the efficacy of single-stage procedures in such cases.